THE USE OF THERMAL HARDENING ELEMENTS OF RAILWAY WHEELS TO IMPROVE THE OPERATIONAL RELIABILITY - Vakulenko, I. A.; Perkov, O. M. (Science and Transport Progress, 2008)
In the article the solution of urgent scientific and technical problem is considered – the development of technology of hardening thermal treatment of railroad wheels.